USING LANGUAGE GAMES TO IMPROVE ENGLISH PROFICIENCY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article examines the use of language games as an effective tool for enhancing English proficiency. Language games can make learning engaging and enjoyable while providing opportunities for practice in a relaxed setting. The article explores different types of language games, including word games, sentence games, and role-playing activities, and discusses their benefits in language learning. It also offers practical examples and strategies for integrating language games into classroom instruction to improve various aspects of language skills.